Comparative Analysis The Effect of Iodine, Ozone, and Peracetic Acid as A Disinfectant of Cantang Grouper Egg - Puspanjali, Putu Justika Nirmala Ardhiana; Yudasmara, Gede Ari; Antara, Kadek Lila (Advances in Tropical Biodiversity and Environmental Sciences; Vol 5 No 3 (2021): ATBES, 2021)
Problems in the fish hatchery sector often occur such as high egg mortality or low quality of fish eggs. Optimizing biosecurity is one of the efforts to improve the quality of fish eggs, for example by adding disinfectants such as iodine, ozone, and peracetic acid. The use of chemical disinfectants will produce good results if the right dose, time, and commodity are used. In this study. This research aims (1) to determine whether the use of chemicals including iodine, ozone, and peracetic acid had an effect as a disinfectant to increase the hatching rate of grouper fish, (2) to determine the level of effectiveness and efficiency of the use of chemicals as a disinfectant. This research is an experimental research type. The research subjects included in the study were cantang grouper fish eggs at PT. Pakarti Daksa Segara who used the exploratory sampling method. The conclusion of this study indicates that there is an influence on the growth rate of the use of iodine, ozone and, peracetic acid chemicals as disinfectants of cantang grouper eggs and there is a comparison of the effectiveness and efficiency of the use of the three chemicals which includes the percentage of the hatching rate, the cost of the disinfectant material and the time, which is needed in the use of the disinfectant. Iodine has the best level of effectiveness from the comparison of hatching eggs of cantang grouper and peracetic acid is the most efficient type of chemical.